THE EFFECT OF PRODUCT QUALITY AND PRODUCT INNOVATION ON CONSUMER LOYALTY IN FIZZUL PUTRA MANDIRI CONVECTION, JOMBANG REGENCY - Rahayu Somalua; Asim; Nurminingsih; Robert Siregar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The purpose of this study is to analyze the effect of Product Quality and Product Innovation on Consumer Loyalty of Fizzul Putra Mandiri Convection, Jombang Regency. This research is a quantitative study, while the population in this study are consumers from the Fizzul Putra Mandiri Convection Jombang regency, which are included in the population of regular (customers) in which the sample to be taken is known with certainty, resulting as many as 85 regular consumers. The data was obtained using a questionnaire, the data was processed using the Structural Equation Model (SEM) or SmartPLS 3 software. The results reveal that product quality has an insignificant positive effect on consumer loyalty, which means that the higher the product quality, the higher the consumer loyalty, but the increase in consumer loyalty caused by product quality is not significant. Therefore, increasing product quality only slightly increases consumer loyalty, decreasing product quality only slightly decreases consumer loyalty. Meanwhile, product innovation has a positive and significant effect on consumer loyalty, which means the higher the product innovation, the higher the consumer loyalty and vice versa. Besides that, product quality has a positive and significant effect on product innovation, which means that the higher the product quality, the higher the product innovation, and the lower the product quality will result the lower the product innovation as well.